Kinetic Modeling of Adsorption of Pb(II) Using Activated Carbon Prepared from Lapsi Seed Stone by Chemical Carbonization - Shrestha, Rajeshwar Man (Journal of Nepal Chemical Society, 2017)
Available with full text.